2008
DOI: 10.1016/j.yhbeh.2008.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of estradiol influence on spatial tasks and hippocampal CA1 spines: Evidence that the duration of hormone deprivation after ovariectomy compromises 17β-estradiol effectiveness in altering CA1 spines

Abstract: Two pulses of 17β-estradiol (10µg) are commonly used to increase hippocampal CA1 apical dendritic spine density and alter spatial performance in ovariectomized (OVX) female rats, but rarely are the measures combined. The goal of this study was to use this two-pulse injection protocol repeatedly with intervening wash-out periods in the same rats to: 1) measure spatial ability using different tasks that require hippocampal function and 2) determine whether ovarian hormone depletion for an extended 10-week period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
82
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 95 publications
(138 reference statements)
11
82
2
Order By: Relevance
“…A recent study by Snyder et al (27) confirms our original finding that E2 increases synaptic NR2B-mediated current, and because these authors did not find an increase in NR2B expression, they suggested that the increase in current was due to lateral movement of NR2B-containing receptors into the synapse. However, in contrast to our findings and those of Snyder et al (27), Adams et al (38) reported no increase in NR2B-containing receptors in synapses of young animals treated with E2. Other studies have found no increase in axospinous synapse or dendritic spine densities in E2-treated aged animals (39,40).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A recent study by Snyder et al (27) confirms our original finding that E2 increases synaptic NR2B-mediated current, and because these authors did not find an increase in NR2B expression, they suggested that the increase in current was due to lateral movement of NR2B-containing receptors into the synapse. However, in contrast to our findings and those of Snyder et al (27), Adams et al (38) reported no increase in NR2B-containing receptors in synapses of young animals treated with E2. Other studies have found no increase in axospinous synapse or dendritic spine densities in E2-treated aged animals (39,40).…”
Section: Discussioncontrasting
confidence: 99%
“…This increase in NR2B current is consistent with results from 23-to 24-mo-old rats, in which E2 was found to stimulate lateral movement of NR2B-containing NMDARs into the synapse (38). A recent study by Snyder et al (27) confirms our original finding that E2 increases synaptic NR2B-mediated current, and because these authors did not find an increase in NR2B expression, they suggested that the increase in current was due to lateral movement of NR2B-containing receptors into the synapse.…”
Section: Discussionsupporting
confidence: 91%
“…The open field and object location/recognition procedures for this experiment were implemented as previously described (McLaughlin et al 2008). For the open field, rats were placed in the arena and allowed to explore for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that PFCX and sex will influence acquisition, extinction, and recall of extinction in fear conditioning. Given the dearth of studies using females and to further characterize the effects of PFCX on behavior, we then tested sham and PFCX male and female rats on several other tasks that have been used in past studies following chronic stress and may be influenced, in part, by PFC function, including the Y-maze (Conrad et al 2004;McLaughlin et al 2007), object location (Beck and Luine 2002;McLaughlin et al 2008), and object recognition (Beck and Luine 2002). Figure 1 illustrates the time line leading up to brain processing.…”
mentioning
confidence: 99%
“…Published November 12, 2010. Estrogen receptors affect several neurotransmission systems in many areas, including the catecholaminergic, serotoninergic and gabaergic ones, interfering with cognitive functioning. One of the actions of estrogen is to enhance the density of the dendritic spines in the neurons of the CA1 area in the hippocampus (1). Progesterone contributes to the same action within 6-8 h of ingestion, and returns to basal levels rapidly (2).…”
Section: Introductionmentioning
confidence: 99%